The Impact of Smart City Construction on the Quality of Foreign Direct Investment in China. (23rd August 2021) - Ye, Chong; Zhao, Zhaoyang; Cai, Jinlong
Abstract : As a new model of urban development, it is important to scientifically analyze the impact of smart cities on the quality of foreign direct investment (FDI). This article constructs a difference in differences' model to test the impact of foreign direct investment quality in smart city construction based on panel data of 226 prefecture-level cities from 2006–2017. Study shows the following. (1) The construction of smart cities has significantly improved the quality of FDI utilized in pilot cities. (2) Heterogeneity analysis shows that smart city construction significantly contributes to the quality of FDI in the western city subsample and a subsample of cities with low natural resource dependence. After a series of robustness tests and placebo tests, the above conclusions still hold. The results of the study suggest that China should further promote the construction of smart cities to optimize the quality of foreign direct investment and promote high-quality economic growth. The findings of the study also provide theoretical and practical references for the construction of smart cities in China and other countries around the world.